Distribution of tight junctions in the primate cochlear lateral wall. (19th January 2020) - Saeki, Tsubasa; Hosoya, Makoto; Shibata, Shinsuke; Okano, Hideyuki; Fujioka, Masato; Ogawa, Kaoru
Highlights: We investigated the distribution of TJs in primate cochlear lateral wall. TJs are similarly distributed around primate and rodent cochlear lateral wall. The result will help to predict the permeability of drugs targeting cochlear cells in humans by performing rodent experiments. Abstract: The blood-labyrinth barrier (BLB) is a major structure that separates the inner ear from the systemic blood circulation. Many drugs cannot access the inner ear because of their inability to cross the BLB. In the cochlea, the BLB is mainly distributed in the lateral wall. However, the ultrastructure of the cochlear lateral wall, including the distribution of tight junctions (TJs), which are its main component, has not been thoroughly examined in primates. This study investigated the distribution of TJs in the cochlear lateral wall of the common marmoset by performing immunohistochemistry for TJ markers and transmission electron microscopy. As previously reported in rodents, TJs were distributed at the lumenal side of stria marginal cells and basal cells. In outer sulcus cells, which are more developed in primates than in rodents, TJs were distributed at the side with the endolymph but not at the side with the spiral ligament, where many capillaries were located. These findings indicate that drugs and small compounds circulating systemically in the blood can easily access outer sulcus cells, but have a limited ability to enter endolymph. No structural differences were detected between species, indicating that the in vivo distribution of drugs in cochlear lateral wall cells, including outer sulcus cells, in primates can be predicted by performing rodent experiments.